PENGARUH PERBEDAAN SUHU DAN LAMA PENYIMPANAN TERHADAP KUALITAS FISIK TELUR AYAM RAS - Syaifulloh Muchammad; Edya Moelia Moeis (AVES: Jurnal Ilmu Peternakan, 2021)
The research begins June – July 2021 at the Laboratory of the Faculty of Animal Husbandry, Balitar Islamic University. This study used an experimental method using a completely randomized design (RAL) with a 2x5 factorial pattern with 5 replications. Factor A is room temperature and temperature <10°C, Factor B is storage for 0 days, 1 day, 3 days, 7 days and 14 days. The changes observed were the value of egg white index, egg yolk index and haugt unit. The results showed that temperature and storage had a significant effect (P<0.05) on the egg white index, the interaction between temperature and storage time had no significant effect (P>0.05) on the egg white index. temperature and storage time had a significant effect on the yolk index and haugt unit index values. The interaction between temperature and storage time had a significant effect (P<0.05) on the index value of egg yolk and egg white. The effect can be seen from the decrease in the value of the egg yolk index, egg white index and haugt unit. The conclusion of this study is that eggs stored at room temperature are not stored for more than 3 days because on the 7th day there is a significant decrease in value, while those stored at temperatures <10°C can maintain egg quality in the good category until a shelf life of 14 days.